2018
DOI: 10.1186/s12964-018-0240-3
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting SOD1 activity inhibits cell growth and enhances lipid accumulation in nasopharyngeal carcinoma

Abstract: BackgroundSOD1 is an abundant enzyme that has been studied as a regulator of the antioxidant defence system, and this enzyme is well known for catalyzing the dismutation of superoxide into hydrogen peroxide. However the SOD1 in the progress of NPC and underlying mechanisms remain unclear.MethodsIn NPC tissue samples, SOD1 protein levels were measured by Western blot and immunohistochemical (IHC) staining. mRNA levels and SOD1 activity were monitored by qRT-PCR and SOD activity kit, respectively. Kaplan-Meier s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…5m). These results are consistent with previous reports of the induction of apoptosis in established cancer cell lines following treatment with SOD1 inhibitors 2,3,40,44 .…”
Section: Resultssupporting
confidence: 93%
“…5m). These results are consistent with previous reports of the induction of apoptosis in established cancer cell lines following treatment with SOD1 inhibitors 2,3,40,44 .…”
Section: Resultssupporting
confidence: 93%
“…They further showed that increased hydrogen peroxide levels leads to p38 MAPK activation and subsequently results in a decrease in the anti-apoptotic factor MCL1 98 . It was also recently reported that SOD1 inhibition in nasopharyngeal carcinoma inhibits cell growth and promotes apoptosis 99 . These observations suggest that one mechanism by which SOD1 inhibition reduces cancer cell growth is through apoptosis.…”
Section: Sod1 In Cancermentioning
confidence: 94%
“…polymorphisms have contributions to the most nonfamilial dyslipidemia with complex molecular mechanisms. The previous animal studies demonstrated the antioxidant role of SOD1 to modulate the redox homeostasis in lipid metabolism [13][14][15], and cholesterol metabolism was affected by SOD1 even independent of its antioxidant activity via inhibiting the activity of 3-hydroxy-3-methylglutaryl CoA reductase and promoting the low-density lipoprotein receptor pathway in hepatocarcinoma cells [16]. SOD1 was also bound to almost all classes of circulating lipoproteins with relative high activity in low and high density lipoproteins [7], which partly underlay its potential in lipid metabolism.…”
Section: Plos Onementioning
confidence: 99%
“…Supraphysiological levels of ROS are extremely detrimental to DNA, lipids, proteins, and normal cellular metabolism [10,11], and have a strong potential to disturb the lipid metabolism [12]. The Sod1 knockout mice were characterized by lipid accumulation in liver and abnormal circulating lipid profiles [13,14], and the inhibition of SOD1 function in nasopharyngeal carcinoma connived the accumulation of lipid droplets [15]. SOD1 also affected cholesterol metabolism in human hepatocarcinoma cells [16] and its presence in human serum lipoproteins suggested its crucial role in the lipid transport [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation